Analisis Pendapatan Usaha Gula Aren Robert Moningka Di Desa Agotey Kecamatan Mandolang - Runtulalo, Gherry; Sendow, Martha Mareyke; Benu, Olfie Liesje Suzana (Sam Ratulangi University, 2023)
This study aims to analyze the income of Robert Moningka's palm sugar business in Agotey Village, Mandolang District. Data analysis used in this study is quantitative data analysis, then analyzed using profit analysis by calculating the difference between revenue and costs used. The data collection method in this study was carried out by collecting primary data and secondary data. Primary data were obtained from interviews conducted directly by the researcher to Mr. Robert Moningka with questions that had been prepared previously by the researcher. While secondary data obtained from government agencies that are in accordance with the research. The results of this study show that Mr. Robert's palm sugar business income in Agotey Village, Mandolang District, Minahasa Regency, in 1 month or 30 days the average income is Rp. 9,600,000. Cost Rp 723,166.66. Income Rp 8,876,833.34.